2021
DOI: 10.1101/2021.01.30.426796
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multicellular immune hubs and their organization in MMRd and MMRp colorectal cancer

Abstract: Immune responses to cancer are highly variable, with mismatch repair-deficient (MMRd) tumors exhibiting more anti-tumor immunity than mismatch repair-proficient (MMRp) tumors. To understand the rules governing these varied responses, we transcriptionally profiled 371,223 cells from colorectal tumors and adjacent normal tissues of 28 MMRp and 34 MMRd patients. Analysis of 88 cell subsets and their 204 associated gene expression programs revealed extensive transcriptional and spatial remodeling across tumors. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 86 publications
(127 reference statements)
1
10
0
Order By: Relevance
“…For example, cancers with high expression of genes indicative of epithelial-to-mesenchymal transition exhibit a distinct, suppressed immune landscape 77 . Single cell sequencing studies have shown that transcriptional profiles of immune and cancer cells can co-vary and suggest the existence of recurring “hubs” of interacting cells 78 . Genes that are characteristic of such hubs would be expected to capture particularly high levels of variance, as they would be predictive of both immune and tumor cell transcriptomes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cancers with high expression of genes indicative of epithelial-to-mesenchymal transition exhibit a distinct, suppressed immune landscape 77 . Single cell sequencing studies have shown that transcriptional profiles of immune and cancer cells can co-vary and suggest the existence of recurring “hubs” of interacting cells 78 . Genes that are characteristic of such hubs would be expected to capture particularly high levels of variance, as they would be predictive of both immune and tumor cell transcriptomes.…”
Section: Discussionmentioning
confidence: 99%
“…They found 'hotspots of immune activity' comprised of chemokine-expressing malignant and non-malignant cells adjacent to activated T cells. 118 In tumours, there are active communications between different cell types, including tumour cells, through various signaling pathways. Identifying the communications between tumour and non-tumour cells will provide important insights into the development of novel therapeutic strategies.…”
Section: Applications Of Single-cell Rna Sequencingmentioning
confidence: 99%
“…In addition, recently Pelka and colleagues developed a systematic approach to apply on two most common type of human colorectal cancer, mismatch repair deficient (MMRd) and MMR proficient (MMRp) tumours, discovering cell types, their underlying programs and cellular communities. They found ‘hotspots of immune activity’ comprised of chemokine‐expressing malignant and non‐malignant cells adjacent to activated T cells 118 …”
Section: Applications Of Single‐cell Rna Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…ICI treatment failure in patients with MSI-H cancers is associated with elevation of the neutrophil-to-lymphocyte ratio in peripheral blood Given the well-established limitations of standard single-cell RNA sequencing technologies to study neutrophils 54 , we sought to test our hypotheses regarding neutrophils using additional human datasets. Recently, a multicellular and molecular inflammatory hub composed of NF-kB transcription factors, inflammatory tumour cells, lymphocytes, neutrophils, and neutrophil-attracting chemokines has been described in human colorectal cancer (COAD) 55 . We hypothesized that within a TME capable of upregulating such NF-kB-dependent, neutrophil-recruiting inflammation, MSI-H status and the accompanying increased T cell infiltration 56,57 would result in an increase in neutrophils in the TME.…”
Section: Ici Treatment Induces Tnf+ Cd8 T Cells Associated With Incre...mentioning
confidence: 99%